2019
DOI: 10.3389/fphar.2019.00782
|View full text |Cite
|
Sign up to set email alerts
|

The Essential Oils and Eucalyptol From Artemisia vulgaris L. Prevent Acetaminophen-Induced Liver Injury by Activating Nrf2–Keap1 and Enhancing APAP Clearance Through Non-Toxic Metabolic Pathway

Abstract: Artemisia has long been used in traditional medicine and as a food source for different functions in eastern Asia. Artemisia vulgaris L. (AV) is a species of the genus Artemisia. Essential oils (EOs) were extracted from AV by subcritical butane extraction. EO contents were detected by electronic nose and headspace solid-phase microextraction coupled with gas chromatography (HS-SPME-GC-MS). To investigate the hepatoprotective effects, mice subjected to liver injury were treated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
39
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(42 citation statements)
references
References 44 publications
2
39
0
1
Order By: Relevance
“…Our results showed that the 24 h treatment of HaCaT cells with EOs affected TAS levels in a dose-dependent manner. These results are in accordance with previous studies [59][60][61], where essential oils increased the antioxidant effects in in vitro and in vivo systems (HepG2, IEC-6, hepatocytes of rat and mice). The results of Placha et al [62] demonstrated that lower concentrations of EOs improve the health status of animals.…”
Section: Discussionsupporting
confidence: 93%
“…Our results showed that the 24 h treatment of HaCaT cells with EOs affected TAS levels in a dose-dependent manner. These results are in accordance with previous studies [59][60][61], where essential oils increased the antioxidant effects in in vitro and in vivo systems (HepG2, IEC-6, hepatocytes of rat and mice). The results of Placha et al [62] demonstrated that lower concentrations of EOs improve the health status of animals.…”
Section: Discussionsupporting
confidence: 93%
“…In addition, nuclear factor erythroid 2-related factor 2 (Nrf2), a transcription factor that is involved in cellular responses to oxidative damage and inflammation, is also regulated by several terpenes. Previous studies have shown that α-pinene, β-caryophyllene, borneol, 1,8-cineole, and linalool up-regulated Nrf2 activity to protect cells from oxidative damage [72,[128][129][130][131]. However, in the case of terpenes other than linalool, it is unclear whether the increased Nrf2 activity by these terpenes is associated with their anti-inflammatory action.…”
Section: Regulation Of Transcription Factors Involved In Inflammatorymentioning
confidence: 99%
“…Previous studies have shown that essential oil has hepatoprotective effects in various animal models (Bouzenna et al, 2016[ 14 ]; Jiang et al, 2019[ 43 ]; Morales-López et al, 2017[ 58 ]; Özbek et al, 2016[ 62 ]; Selmi et al, 2015[ 73 ]). P. minus contains various medicinal values and yields high levels of essential oil (72.54 %) mainly of aliphatic aldehydes, terpenoids and organic acids (Baharum et al, 2010[ 10 ]).…”
Section: Introductionmentioning
confidence: 99%